Neuromusicology or Musiconeurology? “Omni-art” in Alexander Scriabin as a Fount of Ideas - Triarhou, Lazaros C. (Frontiers in Psychology, 2016)
Science can uncover neural mechanisms by looking at the work of artists. The ingenuity of a titan of classical music, the Russian composer Alexander Scriabin (1872–1915), in combining all the sensory modalities into a polyphony of aesthetical experience, and his creation of a chord based on fourths rather than the conventional thirds are proposed as putative points of departure for insight, in future studies, into the neural processes that underlie the perception of beauty, individually or universally. Scriabin’s “Omni-art” was a new synthesis of music, philosophy and religion, and a new aesthetic language, a unification of music, vision, olfaction, drama, poetry, dance, image and conceptualization, all governed by logic, in the quest for the integrative action of the human mind toward a “higher reality” of which music is only a component.